Contrasting Quantitative and Qualitative Approaches to Rural Development Analysis: The Case of Agricultural Intensification in Lebanon. (3rd December 2014) - Hamade, Kanj; Malorgio, Giulio; Midmore, Peter
Abstract: While peripheral rural regions in Lebanon face typical problems of lagging development and economic marginalisation, they have not been regarded as a priority for policy‐makers. Local extensionists have encouraged technological innovation as a means of improving farmers' livelihoods, and this has led to increasing input use and an intensification of agricultural production. This paper applies contrasting quantitative and qualitative methodologies to analyse the effects of such changes at the level of the overall economy of Lebanon and also to explore the impacts on rural households. A computable general equilibrium (CGE) model simulates shocks in which agricultural output increases due to different types of intensification. The results are contrasted at local level through the use of qualitative case study analysis carried out in the Hermel district of northeast Lebanon. Quantitative simulations indicate that, while agricultural intensification has a positive effect overall on the Lebanese economy, the effects on rural households and the income of farmers are negative. The case‐study interviews demonstrate that, at local level, agricultural trade liberalisation, increased agricultural output and greater volatility of commodity prices have resulted in farmers opting for lower input use and more secure market forms of production.